The Use of Storytelling Technique with Picture Series in Teaching Speaking - Nurul Fajriani; Asnawi Muslem; Kismullah Abdul Muthalib (Proceedings of AICS - Social Sciences, 2021)
The first grade students of State Senior High School 1 Gandapura batch 2020/2021 were having problems in speaking skill and yet they are expected to be able to express ideas in the interpersonal, transactional, and functional communication. Storytelling has been extensively implemented in the learning process and shows a significant result on students’ speaking skill. However, no study had ever highlighted an important gap in the literature about students’ anxiety in using storytelling technique with picture series. This study aims to find out the significant difference in achievement between students who are taught by using storytelling technique with picture series and those who are not taught by using storytelling technique with picture series. Furthermore, it explores students’ anxiety in using storytelling techniques with picture series. Two classes were randomly selected for the sample of the study. Tests and questionnaires were used to collect the data. It was analyzed by using SPSS and Microsoft Excel. The finding shows that the students’ achievement in the experimental class group were significantly improved than those of the control class group in terms of speaking in English. In addition, most of the students experienced high level anxiety when they had little time to think about what they had to say in English as well as when their oral skills were tested. Subsequently, the students are likely to experience low level anxiety due to their poor pronunciation and intonation. However, they experienced a moderate level of anxiety when the storytelling technique with picture series was used in speaking.Keywords: Speaking; storytelling technique; picture series; teaching speaking.